Analysis of C-organic and total Phospor (P2O5) contents of soil around egg-laying chicken farm. Issue 1 (April 2020) - Abdullahi, A B; Siregar, A R; Pakiding, W; Mahyuddin,
Abstract: Sustainable animal husbandry development should be environmentally friendly, meaning it doesn't cause pollution and degradation of environmental quality, i.e. technically efficient, economically fit for use, socially acceptable and ecologically still ensuring the balance of other ecosystems. One of the resources which should be noted is the soil condition around the farm which is suspected to have degraded quality due to pollutions caused by farming activities. Based on that, the environmental test was performed by analyzing the C-Organic and Total Phosphor (P2 O5 ) contents of soil around the egg-laying chicken farm. The present study was aimed to (1) know the C-Organic and P2 O5 contents of soil around the egg-laying chicken farm; (2) compare the C-Organic and P2 O5 contents of soil around the egg-laying chicken farm with the set assessment criteria for soil chemical properties (C-Organic and P2 O5 ) for farmland. The present study was performed on October-December 2018, soil samples were obtained from locations around egg-laying chicken farms in Sidenreng Rappang Regency, South Sulawesi, Indonesia. The method used in testing the C-Organic and P2 O5 contents of soil was spectrophotometric. The working procedure in the present study: (1) testing the C-Organic and P2 O5 contents of soil in the location and around egg-laying chicken farm; (2) comparing the C-Organic and P2 O5 contents of soil from the research result with the set assessment criteria of soil chemical properties (C-Organic and P2 O5 ) for farmland. The research result showed that the average C-Organic content of the soil around the egg-laying chicken farm was 0.699% and the average P2 O5 content of the soil around the egg-laying chicken farm was 159.2 mg/100 g. Based on the results, it's concluded that the content of C-Organic soil around the egg-laying chicken farm is very low because < 1.0 % but P2 O5 very high because of > 60 mg/100 g.